2014
DOI: 10.1055/s-0034-1377442
|View full text |Cite
|
Sign up to set email alerts
|

Transcardiac tunneling technique for endoscopic submucosal dissection of gastric fundus tumors arising from the muscularis propria

Abstract: The promising endoscopic resection techniques for upper gastrointestinal submucosal tumors (SMTs) are challenged when performed in the gastric fundus. Here, we report on the development of a transcardiac endoscopic tunneling technique (TCTT) for the resection of tumors in this area. A total of 18 patients with gastric fundus SMTs arising from the muscularis propria on endoscopic ultrasound underwent TCTT. The procedure involved the excavation of a submucosal tunnel from the esophagus, through the cardia, to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
39
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 9 publications
(17 reference statements)
1
39
0
Order By: Relevance
“…To our knowledge, our study contains the largest number of GIST in the UGIT resected by the endoscopic procedure, considering that previous studies only included small number of case series attached to clinical data of gastric SETs resected by ESD, STER or EFTR, [15][16][17][18][19][20][27][28][29][30] and their follow-up duration was relatively short, ranging from 2 to 21 months, 15,17,20,27,28,30,31 or even not presented. 16,18,29 Endoscopically resected cases in our study were followed up for 46 months on average, longer than previous studies, but nevertheless, the recurrence rate was 2.2%. This was compatible with previously published data reporting no recurrence during relatively shortterm duration of follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, our study contains the largest number of GIST in the UGIT resected by the endoscopic procedure, considering that previous studies only included small number of case series attached to clinical data of gastric SETs resected by ESD, STER or EFTR, [15][16][17][18][19][20][27][28][29][30] and their follow-up duration was relatively short, ranging from 2 to 21 months, 15,17,20,27,28,30,31 or even not presented. 16,18,29 Endoscopically resected cases in our study were followed up for 46 months on average, longer than previous studies, but nevertheless, the recurrence rate was 2.2%. This was compatible with previously published data reporting no recurrence during relatively shortterm duration of follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…Although the majority of the SMTs in the MP layer are solitary, multiple studies have reported the presence of multiple SMTs (11,13,18,19,21,22). Chen et al (21) reported a patient simultaneously exhibiting esophageal and cardia SMT, and the two SMTs were successfully removed using STER with a single tunnel.…”
Section: Applications Of Stermentioning
confidence: 99%
“…Currently, >20 studies have been published with outcome data based on >700 patients (6)(7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)22,29,30,(32)(33)(34)(35). In these studies, therapeutic success was recorded for >77% of patients and en bloc resection was achieved in >85% of patients, while irregularly shaped or larger tumors were risk factors in piecemeal resection (33).…”
Section: Efficacy Of Stermentioning
confidence: 99%
See 1 more Smart Citation
“…Endoscopic full-thickness resection (EFTR) has proved to be a safe and effective endoscopic method for the treatment of gastric fundus SMTs that originate from the muscularis propria (MP) layer, with a high rate of complete resection (5)(6)(7)(8)(9)(10). Submucosal tunneling endoscopic resection (STER) is a novel endoscopic technique and has been shown to be safe and effective for the treatment of gastric SMTs (11)(12)(13)(14). However, there is little data that compares STER and EFTR for the treatment of SMTs in the gastric fundus.…”
Section: Introductionmentioning
confidence: 99%